Feasibility Analysis of a Precast Concrete Business in the Remote Areas of Tanjung Sauh Island Using the Tlmbc Approach - Sherly Tano (Eduvest - Journal of Universal Studies, 2026)
This study examines the business feasibility of establishing a precast concrete plant in Tanjung Sauh Special Economic Zone (SEZ), Batam, using the Triple Layered Business Model Canvas (TLBMC) framework. Tanjung Sauh SEZ is projected to attract IDR 199.6 trillion in investment and create over 360,000 jobs by 2053, yet faces a structural challenge of no land access to Batam, resulting in material cost increases of 20 to 30 percent and delivery delays of two to three weeks per cycle. This study employed a descriptive qualitative approach with a prospective single case study design, collecting data through field observation, semi-structured interviews with eight purposively selected informants, and document analysis, validated through source, method, and data triangulation. Findings confirm multidimensional feasibility: economically through an IRR of 24 percent, four-year payback period, positive NPV, and 25 percent cost efficiency reinforced by KEK fiscal incentives; environmentally through 25 to 30 percent transport CO₂ emission reduction, fly ash substitution, and circular economy principles; and socially through a minimum 70 percent local workforce commitment, comprehensive occupational safety management, and ESG governance. The three layers form a self-reinforcing causal chain, making this business model systemically sustainable.